Let-down stability and screen printability of inks prepared using non-printing ink grades of carbon black pigment. Issue 6 (4th November 2019) - Ali, Muhammad; Lin, Long; Faisal, Saira; Ali, Syed Rizwan; Ali, Syed Imran
Abstract : Purpose: This paper aims to analyse the let-down stability of the binder-free dispersion of non-printing ink grades of carbon black and to assess the screen-printability of the finished inks formulated thereof from these pigment dispersions. Design/methodology/approach: Binder-free pigment dispersions that were prepared and optimised following a ladder series of experiments (reported in a separate study by the authors) were let-down with three different binders such that inks containing various amounts of a binder were prepared followed by a rheological characterisation immediately after formulation and after four weeks of storage. The screen printability of the inks that displayed considerable stability was assessed, so was the ink film integrity. Findings: The pigment dispersions that were considered in the present study were generally found to be stable after let-down with different binders. This was indicated by the fact that the finished inks possessed a shear thinning viscosity profiles, after formulation and after storage, in most of the cases. Furthermore, the screen printability of the inks was also found to be good in terms of registration quality of a selected design. The structure of the ink film deposits on uncoated and binder-coated textile fabrics was also highly integrated and free from discontinuities. Originality/value: Carbon blacks with very low volatile matter content and/or high surface area are generally not considered suitable for use in the formulation of printing inks. This is because of their generally poor dispersability and inability to form dispersions that remain stable over extended periods. This work, which is a part of a larger study by the authors, concerns with the stability of inks formulated from binder-free dispersions of such non-printing ink grades of carbon black. The major advantage of using such pigments in inks is that the required functionality is achieved at considerably low pigment loadings.